Correlation Between Intensity of Screen Time To Aspect Receptive Language Development on Toddlers At Dinoyo Public Health Center - Hasanah, Annisa; Zahrany, Nadika; Rahayu, Rahayu; Sidharta, Bragastio (Journal of Aafiyah Health Research (JAHR), 2024)
Background: Screen time exposure have an impact to children's speech delay. Children's speech delays occur when they do not reach age-appropriate communication levels or have inappropriate speech patterns. One of factors causing this delay is related to exposure to electronic media screens (screen time) that is too long or excessive. Excessive exposure can have an impact, one of which is on the development of receptive language in toddlers. Aim: To determine the suitability of the relationship between the intensity of exposure to electronic media screens and aspects of receptive language development in toddlers at the Dinoyo Community Health Center, Malang City. Method: There were a questionnaire regarding the intensity of exposure to electronic media screens and CLAMS (Clinical Linguistic Auditory Milestone Scale) that would be answered by parents or the guardians of these toddlers with aged 1-36 month. Data was analyzed using SPSS software. Results: Toddlers exposured to electronic screen media (screen time) on receptive language development in toddlers aged 1-36 months at the Dinoyo Community Health Center in Malang City were not have a relation or very low correlation (r = 0.061). Conclusion: Our study suggests there is no corellation between screen time and language delays, as other factors play a role. Adhering to AAP screen time guidelines may help reduce delays in children's language and speech development.